Dense cold‐water coral garden of paragorgia johnsoni suggests the importance of the Mid‐atlantic ridge for deep‐sea biodiversity - Morato, Telmo (2022)
Mid-ocean ridges generate a myriad of physical oceanographic processes that favor the supply of food and nutrients to suspension- and filter-feeding organisms, such as cold-water corals and deep-sea sponges. However, the pioneering work conducted along the Mid-Atlantic Ridge failed to report the presence of large and dense living coral reefs, coral gardens, or sponge aggregations. Here, we describe the densest, near-natural, and novel octocoral garden composed of large red and white colonies of Paragorgia johnsoni Gray, 1862 discovered at 545–595 m depth on the slopes of the Mid-Atlantic Ridge, in the Azores region. This newly discovered octocoral garden is a good candidate for protection since it fits many of the FAO criteria that define what constitutes a Vulnerable Marine Ecosystem. The observations described here corroborate the existence of a close relationship between the octocoral structure and the ambient currents on ridge-like topographies, providing new insights into the functioning of mid-ocean ridges' ecosystems. The ubiquitous presence of biogenic and geological topographies associated with mid-ocean ridges, which could act as climate refugia, suggests their global importance for deep-sea biodiversity. A better understanding of the processes involved is, therefore, required. Our observations may inspire future deep-sea research initiatives to narrow existing knowledge gaps of biophysical connections with benthic fauna at small spatial scales along mid-ocean ridges.